1999
DOI: 10.1088/0031-9155/44/7/303
|View full text |Cite
|
Sign up to set email alerts
|

Fricke dosimetry: the difference betweenG(Fe3+) for60Co gamma-rays and high-energy x-rays

Abstract: A calibration of the Fricke dosimeter is a measurement of epsilon G(Fe3+). Although G(Fe3+) is expected to be approximately energy independent for all low-LET radiation, existing data are not adequate to rule out the possibility of changes of a few per cent with beam quality. When a high-precision Fricke dosimeter, which has been calibrated for one particular low-LET beam quality, is used to measure the absorbed dose for another low-LET beam quality, the accuracy of the absorbed dose measurement is limited by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
108
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(129 citation statements)
references
References 45 publications
16
108
0
3
Order By: Relevance
“…The results showed that long term reproducibility is 0.2%. It was found to be similar with data reported for standard Fricke dosimeter in the literature [16]. The results in this study support the conclusion that the FBX is a good practical clinical dosimeter.…”
Section: Resultssupporting
confidence: 91%
“…The results showed that long term reproducibility is 0.2%. It was found to be similar with data reported for standard Fricke dosimeter in the literature [16]. The results in this study support the conclusion that the FBX is a good practical clinical dosimeter.…”
Section: Resultssupporting
confidence: 91%
“…The absorbance readings were corrected for the influence of both the readout temperature, T r , and the irradiation temperature, T i . The linear interval investigated is consistent with the results reported elsewhere [14] and is adequate for radiotherapy purposes. From the result above, by equating D w,F in equation 2 to the absorbed dose to water measured by the reference ionization chamber, D w , we calculate the radiation yield of Fe ) to be 1.598 (±0.012) ”mol j −1 .…”
Section: Calibration Curvesupporting
confidence: 90%
“…First of all it should be emphasized that the overall performance of the developed dosimetric system exhibits typical characteristics of gel dosimeters, like linear response within dose range of interest, 1 , 6 reproducibility, 3 , 6 , 11 tissue‐equivalence, 2 , 3 , 11 and quite negligible photon beam energy dependence 1 , 2 , 5 , 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that dosimetry systems based on FXG have significant advantages: high lighted tissue equivalence, beam quality independence ( a priori , at least to conventional techniques (i.e., not hadronic)), regardless of both quasi‐linear energy transfer 3 , 4 , 5 , 6 , 7 and dose rate 3 , 5 , 8 , 9 . Although diffusion of ferric ions represents a nonnegligible drawback, 1 , 2 , 3 , 10 suitable preparation/manipulation protocols along with prompt analysis provided to FXG the capability to obtain three‐dimensional dosimetry mappings.…”
Section: Introductionmentioning
confidence: 99%